Bioinspired approaches for toughening of fibre reinforced polymer composites - Amorim, Luís Manuel Machado (2021)
In Nature, there are a large range of tough, strong, lightweight and multifunctional structures that can be an inspiration to better performingmaterials. Thiswork presents a review of structures found in Nature, frombiological ceramics and ceramics composites, biological polymers and polymers composites, biological cellular materials, biological elastomers to functional biological materials, and their main tougheningmechanisms, envisaging potential mimicking approaches that can be applied in advanced continuous fibre reinforced polymer (FRP) composite structures. For this, themost common engineering compositemanufacturing processes and current composite damage mitigation approaches are analysed. This aims at establishing the constraints of biomimetic approaches development as these bioinspired structures are to be manufactured by composite technologies. Combining both Nature approaches and engineering composites developments is a route for the design and manufacturing of high mechanical performance and multifunctional composite structures, therefore new bioinspired solutions are proposed.